Communication skills for the health care professional context, concepts, practice, and evidence - Van Servellen, Gwen 1942- (Jones & Bartlett Learning, 2020)
"Communication Skills for the Health Care Professional addresses the connection between communication practices and quality patient care outcomes. It provides future and practicing patient caregivers in all specialties and services with basic communication knowledge and skills and is an invaluable resource for those in administrative functions as well. The Third Edition is a thorough revision that features many new chapters while also combining other chapters for a text that can be used in a single semester course. Features: Provides a psychosocial and physiologic contextual background for understanding sensual development and verbal and nonverbal expression. Teaches communication skills one at a time allowing for contiguous mastery over a set of therapeutic interventions. Includes an extensive glossary of terms and list of references including websites and resources available to enhance student learning."